Comparative Pharmacokinetics and Bioavailability of Epimedin C in Rat after Intramuscular Administration of Epimedin C, a Combination of Four Flavonoid Glycosides and Purified Herba Epimedii Extract - Shunjun Xu; Jiejing Yu; Liu Yang; Yaling Zhu; Shuai Sun; Zhengdi Xu (Journal of Analytical Methods in Chemistry)
Chuan-Ke-Zhi (CKZ), a purified Herba Epimedii extract, is a potent Chinese medicine preparation whose main bioactive components are a class of flavonoid glycosides such as epimedins A, B, and C and icariin. And epimedin C is far more abundant than other flavones in this extract. This study aims to investigate the pharmacokinetic and bioavailability of epimedin C and what effects, if any, other ingredients in CKZ have on its pharmacokinetics. Epimedin C, CKZ, and a combination of epimedins A, B, and C and icariin were, respectively, administrated to rats, and then the pharmacokinetic parameters of epimedin C in the three groups were calculated and compared. The result indicated that CLZ, MRT0–∞, and AUC0–∞ of epimedin C were significantly different among the three groups (P<0.05), and compared with the epimedin C group, the absorption of epimedin C significantly increased in the CKZ group. Furthermore, in this study the absolute bioavailability of epimedin C was also investigated by comparing intramuscular and intravenous administration of epimedin C. As a result, epimedin C could be quickly absorbed with extremely high absolute bioavailability after intramuscular administration.